2018
DOI: 10.1089/lap.2018.0015
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Outcomes of Patients Undergoing Diagnostic Ureteroscopy Before Radical Nephroureterectomy for Upper Urinary Tract Urothelial Carcinomas: A Systematic Review and Meta-Analysis

Abstract: Diagnostic URS before RNU does not seem to compromise long-term survival outcomes, even though it is associated with a higher rate of intravesical recurrence (IVR). Our findings suggest that further investigation, especially through prospective studies, should focus on decreasing the rate of IVR by administration of intravesical chemotherapy immediately after diagnostic URS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Recent multi-centre cohort study conducted by Lee et al showed that delaying RNU for more than three months was associated with poor overall survival, thus, a delay between URS and RNU should not exceed this period [35]. In our meta-analysis we demonstrated that performing URS prior to RNU does not affect long-term oncological outcomes, such as CSS and OS, consistently with previous reports [5,6]. It could be explained by the fact, that reported delay between URS and RNU was not longer than two months in majority of included studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recent multi-centre cohort study conducted by Lee et al showed that delaying RNU for more than three months was associated with poor overall survival, thus, a delay between URS and RNU should not exceed this period [35]. In our meta-analysis we demonstrated that performing URS prior to RNU does not affect long-term oncological outcomes, such as CSS and OS, consistently with previous reports [5,6]. It could be explained by the fact, that reported delay between URS and RNU was not longer than two months in majority of included studies.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the first meta-analysis exploring the risk of IVR associated with URS combined with endoscopic biopsy prior to RNU. Although several studies and previous meta-analyses demonstrated that URS combined with tumour biopsy had no influence on IVR when compared to URS alone (only tumour visualization) [5,6,11,15], the direct comparisons of these subgroups (URS biopsy and URS alone) in reference to patients who did not undergo URS before RNU were not found. Herein, in this study, we found that patients not undergoing tumour biopsy during URS had comparable IVRFS to those diagnosed with UTUC based on imaging studies alone.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first meta-analysis exploring the risk of IVR associated with URS combined with endoscopic biopsy prior to RNU. Although several studies and previous meta-analyses demonstrated that URS combined with tumour biopsy had no influence on IVR when compared to URS alone (only tumour visualization) [ 5 , 6 , 11 , 15 ], the direct comparisons of these subgroups (URS biopsy and URS alone) with reference to patients who did not undergo URS before RNU were not found. Herein, in this study, we found that patients not undergoing tumour biopsy during URS had comparable IVRFS to those diagnosed with UTUC based on imaging studies alone.…”
Section: Discussionmentioning
confidence: 98%
“…According to current recommendations, diagnostic ureteroscopy (URS) should be performed if imaging and cytology are not sufficient for the diagnosis or risk stratification of the tumour [ 2 ]. However, several studies and previous meta-analyses have suggested that preoperative diagnostic URS could increase the IVR rate after RNU (reported in up to 50% of patients), which might be related to malignant urothelial cells backflow and tumour seeding during URS evaluation [ 3 , 4 , 5 , 6 ]. Nevertheless, the existing data are still conflicting.…”
Section: Introductionmentioning
confidence: 99%